Antioxidant Activity of Rhizoma Cibotii in vitro - Wenqiong Mai; Dongfeng Chen; Xican Li (Tabriz University of Medical Sciences, 2012)
Purpose: The paper tried to systematically investigate the in vitro antioxidant activity of Rhizoma Cibotii (RC) for the first time. Method: The methanol extract from RC (MERC) was prepared then systematically investigated by various antioxidant assays, including: DPPH• (1, 1-diphenyl-2-picrylhydrazyl radical), ABTS•+ (3-ethylbenzthiazoline-6- sulfonic acid diammonium salt radical), •O2- (superoxide anion radical), •OH (hydroxyl radical) scavenging assays, Fe3+ reducing power, Cu2+ reducing power assays, compared with positive controls Trolox (± -6 -hydroxyl -2,5, 7, 8-tetramethlychromane-2-carboxylic acid) and BHA (butylated hydroxyanisole). Its total phenolics and caffeic acid content were also measured by Folin-Ciocalteu method and HPLC, respectively. Result: MERC exhibited effective antioxidant activity in dose-dependent manners and its IC50 values were calculated as 44.2 ± 0.62, 19.84 ± 0.31, 137.66 ± 2.90, 22.94 ± 0.90, 289.73 ± 46.17, 53.52 ± 1.51 µg /mL，for DPPH•, ABTS•+, •O2-, •OH scavenging assays, Fe3+ reducing power, Cu2+ reducing power assays, respectively. Its total phenolics content was 50.88 ± 1.24 mg CAE /g and the caffeic acid content was 1.82 ± 0.19 mg/g. Conclusion: Rhizoma Cibotii has effective in vitro antioxidant activity which may attribute to its total phenolics, among which caffeic acid can be considered as one of the active components. The pharmacological effects or healthcare functions of whole RC may result from the synergistic effects caused by the combination of its components and its antioxidant effect plays an important role in the synergistic effects.